Reliable Kinect-based Navigation in Large Indoor Environments - Jalobeanu, Mihai; Shirakyan, Greg; Parent, Gershon; Kikkeri, Harsha; Peasley, Brian; Feniello, Ashley (IEEE International Conference on Robotics and Automation (ICRA), 2015)
Practical mapping and navigation solutions for large indoor environments continue to rely on relatively expensive range scanners, because of their accuracy, range and field of view. Microsoft Kinect on the other hand is inexpensive, is easy to use and has high resolution, but suffers from high noise, shorter range and a limiting field of view. We present a mapping and navigation system that uses the Microsoft Kinect sensor as the sole source of range data and achieves performance comparable to state-of-the-art LIDAR-based systems. We show how we circumvent the main limitations of Kinect to generate usable 2D maps of relatively large spaces and to enable robust navigation in changing and dynamic environments. We use the Benchmark for Robotic Indoor Navigation (BRIN) to quantify and validate the performance of our system.